Nature-Based Engineering: A Review on Reducing Coastal Flood Risk With Mangroves - Gijsman, Rik; Horstman, Erik M.; van der Wal, Daphne; Friess, Daniel A.; Swales, Andrew; Wijnberg, Kathelijne M. (Frontiers in Marine Science, 2021)
Integration of mangroves in projects to reduce coastal flood risk is increasingly being recognised as a sustainable and cost-effective alternative. In addition to the construction of conventional hard flood protection infrastructure, mangroves not only contribute to attenuating flood events (functionality), they also recover in, and adapt to, a changing climate (persistence). The implementation of mangroves in flood risk reduction, however, remains complex. This is because the innate functionality and persistence of mangroves depend on a range of environmental conditions. Importantly, mangroves may collapse when environmental impacts or climatic changes exceed key system thresholds, bringing uncertainty into a situation where failure could endanger lives and livelihoods. The uncertainties in mangrove functionality and persistence can be dealt with by (1) improving insights in how ecological and physical processes affect mangrove functionality and persistence across scales, (2) advancing tools to accurately assess and predict mangrove functionality and persistence, and (3) adopting an adaptive management approach combined with appropriate engineering interventions to enhance mangrove functionality and persistence. Here, we review existing evidence, monitoring techniques and modelling approaches from the viewpoint of mangrove functionality and persistence. Inspired by existing guidelines for Nature-based Solutions (NbS) to reduce flood risk, we provide an operationalization for this new approach. In addition, we identify where further research efforts are required for the practical application of mangroves in coastal flood risk management. Key aspects in the variability and uncertainty of the functionality and persistence of mangroves are their failure and recovery mechanisms, which are greatly site- and storm-specific. We propose five characteristic damage regimes that result in increasing reductions of mangrove functionality as well as post-storm recovery periods. Further research on the quantification of these regimes and their thresholds is required for the successful integration of mangroves in coastal flood risk management. Ultimately, the key challenge is the development of adaptive management strategies to optimise long-term mangrove functionality and persistence, or their resilience. Such adaptive strategies should be informed by continued mangrove functionality and persistence assessments, based on continued monitoring and modelling of key mangrove thresholds, and supported through well-established guidelines.